LI YANG CRAZY ENGLISH METHOD; BETWEEN CHINESE AND JAVANESE CULTURE - Dania, Maya (English Education Department, Universitas Islam Indonesia, 2010)
Nowadays English is spoken everywhere. English has become the world's Lingua Franca. Many jobs demand English as their first priority to select applicants. Schools push their students to learn English since it becomes the most favorite qualification for getting job. Many English courses are built in order to facilitate people's needs to understand English. Nevertheless, along with the world's request on English, many people in non-spoken English country still feel unfamiliar to it. It creates some anxiety and terror to them.In China, there is a unique language-learning method to deal with English fear. It is called Crazy English. Li Yang, a man who initiated this method, believed that many Chinese were facing a very difficult time on learning English. He then coined an extra-ordinary way to make people proficient in English by especially emphasizing the speaking and pronunciation skills. Based on his method, he taught his students to read English words loudly and quickly, and also told them to imitate the sound of English words. He had already proved himself that by conducting this methods he was able to get the second-highest score on his National English Exams after failing it thirteen times; For Li Yang, the only main obstacle on learning English was the Chinese's traditional culture that made people afraid to talk. He suggested people to overcome English by shouting and speaking it loudly, so that all the embarrassment could fade away.Comparing with Chinese, Javanese people have also the same problem related to the afraid-to-talk culture. Based on writer's experience in class, many students feel shy and unconfident to speak English. It makes a very tough problem when learning English is not followed by the courage to speak.This paper is aimed to investigate the Li Yang Crazy English method and evaluate its potential aspect to be applied in many English classes in Indonesia, particularly in Java region. The analysis of this paper is taken from literature research and it is also supported by performing in-class observation. As the result of the research, this paper will give a clear understanding about Li Yang Crazy English and also its potential aspect to be applied in Indonesia by giving three main considerations, such as: 1)The general evaluation of positive and negative aspects from Li Yang English method, 2) The similar cultural background (East culture) of Chinese and Javanese, 3) The readiness of Indonesian teacher to apply this method.